An evaluation of Minor Groove Binders as anti-lung cancer therapeutics. Issue 15 (1st August 2016) - Scott, Fraser J.; Puig-Sellart, Mireia; Khalaf, Abedawn I.; Henderson, Catherine J.; Westrop, Gareth; Watson, David G.; Carter, Katharine; Grant, M. Helen; Suckling, Colin J.
Graphical abstract: A distamycin derived minor groove binder with superior in vitro anti-lung cancer activity to Gemcitabine. Highlights: Minor Groove Binders (MGBs) possess activity against the melanoma cancer cell line B16-F10. 5 MGBs have been identified that have IC50 s less than that of a standard therapy, Gemcitabine. Lead compound around >70 more active than Gemcitabine and a favourable selectivity index of >125. Abstract: A series of 47 structurally diverse MGBs, derived from the natural product distamycin, was evaluated for anti-lung cancer activity by screening against the melanoma cancer cell line B16-F10. Five compounds have been found to possess significant activity, more so than a standard therapy, Gemcitabine. Moreover, one compound has been found to have an activity around 70-fold that of Gemcitabine and has a favourable selectivity index of greater than 125. Furthermore, initial studies have revealed this compound to be metabolically stable and thus it represents a lead for further optimisation towards a novel treatment for lung cancer.